Crafting virtual reality. Issue 2 (1st December 2018) - Heller, Lynne
This text describes, illustrates and theorizes the creation of a virtual reality (VR) landscape/game/sojourn, titled One for Sorrow, an artwork that seeks to confound the dichotomies between hand and digital making and the illusion of two dimensionality versus three dimensionality. This text also describes the making process as a way to position and trouble the translation of the handmade into the digital using collage, assemblage and montage along with craft theory. Although ostensibly a firstperson puzzle game, the experience uses the old nursery rhyme One for Sorrow to entice the player to explore and discover, not necessarily mixed realities, but rather, mixed sensibilities – 2D/3D, hand/algorithm, drawn/photographic. Digital and handmade aesthetics, coupled with considered sound design and narrative, can evoke an immersive experience and provide an unorthodox model for VR art.